Alternatives For Providing Compensation For The Detention Of A Defendant Whose Case Is Acquitted - Aristian Akbar (Fakultas Hukum Universitas Lampung, 2022)
Pretrial is still a paradox that creates uncertainty in compensating defendants who are acquitted and have permanent legal force. Pretrial is one way to enforce true justice, to enforce law, and truth through horizontal means as regulated in Article 80 of the Criminal Procedure Code to show the essence of pretrial as a form of supervision of coercive measures that have been carried out by investigators and public prosecutors against suspects. Therefore, this study aims to analyze the policy of criminal law regarding the alternative of providing compensation other than through pretrial. This research uses a normative juridical approach and a sociological juridical approach. The data used in this study are secondary data and primary data and use library research and interview instruments. So to the results of this study, there are 2 (two) alternatives for providing compensation for the detention of the defendant whose case was acquitted and had permanent legal force. First, compensation is included in the court decision in case of a loss due to a criminal act. Second, compensation can be made through an Alternative Dispute Resolution (ADR) with a court order. The legal implication when a judge provides compensation for the detention rights of a defendant whose case is acquitted and has permanent legal force is that the state must fulfill its obligation to pay compensation to the defendant. However, if the claim for compensation is rejected, it will result in losses from the accused's social, economic, and human rights aspects.